Schottky mass measurements of heavy neutron-rich nuclides in the element range 70 [less than or equal to] Z [less than or equal to] 79 at the GSI Experimental Storage Ring - Shubina, Daria; Cakirli, R. B.; Litvinov, Yuri A.; Blaum, Klaus; Brandau, C.; Bosch, F.; Carroll, J. J.; Casten, R. F.; Cullen, D. M.; Cullen, I. J.; Deo, A. Y.; Detwiler, B.; et al. (Physical review. C, Nuclear physics, 2013)
Storage-ring mass spectrometry was applied to neutron-rich 197Au projectile fragments. Masses of 181,183Lu, 185,186Hf, 187,188Ta, 191W, and 192,193Re nuclei were measured for the first time. The uncertainty of previously known masses of 189,190W and 195Os nuclei was improved. Observed irregularities on the smooth two-neutron separation energies for Hf and W isotopes are linked to the collectivity phenomena in the corresponding nuclei.
Published 13 August 2013
Im Titel ist [less than or equal to] als mathematisches Zeichen dargestellt
Gesehen am 27.01.2022